The Role Of Lexical Stylistic Devices In Creating Poetic Imagery (Eurasian Journal of Humanities and Social Sciences, 2026)
This article examines the lexical stylistic devices play an essential role in forming the imagery of a poem, functioning as the primary means through which abstract ideas are materialised and emotional experiences are expressed. Imagery in poetry is not merely decorative; it is an integral part of the poem’s semantic and structural organisation. The use of expressive lexical units allows poets to craft vivid pictures that appeal to the reader’s senses, imagination, and intellect. Lexical stylistic devices also contribute to structural cohesion. Imagery created through symbolic or metaphorical vocabulary often recurs throughout the poem, forming thematic unity. Extended metaphors, leitmotifs, and clusters of related symbolic words create semantic coherence and guide the reader’s interpretation.